Рентгеновский динамический дифракционный аналог эффекта Тальбота в случае падающей волны с конечным фронтом - Балян, М. К. (Հայաստանի ԳԱԱ)
X-ray dynamical diffraction Talbot effect is investigated in perfect crystals. The effect is investigated for an incident wave with a restricted wave front. The peculiarities of the effect are revealed, the expressions for the Talbot distance and for the exact Talbot distance are obtained. The results are compared with the results, obtained for the case of a wave with the infinite wave front, in the diffracted beam, previously.
Keywords: X-Ray; Physics